Comparison of Effects of Soy Oil, Olive Oil, Mct-Lct Based Nutrition Solutions in Parenterally Fed Intensive Care Patients - Nurşen Gürsoy; Çetin Kaymak; Ayşe Özcan; Namık Özcan; Turgut Çavuşoğlu; Mustafa Kotanoğlu; Hülya Başar (Galenos Yayinevi, 2012)
Objective: In this study, we aimed to compare the changes in biochemical parameters and efficacy of nutrition by using parenteral nutrition solutions with different lipid content in critically ill patients. Material and Method: Fourty-five intensive care patients were randomized into three groups to receive either soy bean based (Group 1) or olive oil based (Group 2) or MCT/LCT based (Group 3) nutrition solutions. The calorie requirement was calculated using Schofield equation day. The levels of albumin, total protein, AST, ALT, LDH, GGT, ALP, glucose, triglyceride, cholesterol, LDL, HDL, aPTT, PT, INR, CRP, transferin and prealbumin were measured on days 1, 7 and 14. Results: There was no statistically significant difference between groups according to glucose, liver function tests, triglyceride, cholesterol, LDL, HDL, aPTT, PT, INR levels. CRP and prealbumin were similar within-group and between-group comparisons. In groups II and III, CRP levels decreased while prealbumin levels were increasing. Conclusion: As a conclusion, no difference was found comparing the biochemical parameters and efficacy of nutrition, in ICU patients fed with soy oil, olive oil or MCT/LCT based parenteral nutrition solutions. (Journal of the Turkish Society Intensive Care 2012; 10: 52-8)